PROTOTYPE RUMAH KACA BUDIDAYA STROBERI PADA DATARAN RENDAH MENGGUNAKAN IOT - Haris Irnawan; Dani Pradana Kartaputra; Muhamad Iqbal (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2022)
Strawberry plants are fruit plants in the form of herbs. Herbaceous plants are plants that are only up to two meters high. Herbaceous plants have stems that are wet and have no wood. A good location for strawberries is an altitude of 1,000-1,500 meters above sea level, air temperature 14-24o ) and relatively high humidity (85-95%) and does not experience extreme temperatures and humidity. For extreme weather itself, when entering the rainy season, strawberry plants will experience crop failure. There are several supporting factors so that strawberry plants can grow well. There are several supporting factors, including fertilization, watering, automatic temperature regulation, but it is not uncommon for farmers who are busy so that farmers are not maintained. Therefore we need a technology that uses Arduino Uno as a microcontroller that can be automated that makes it easier for farmers to take care of their strawberry plants.